Essential newborn care practices and associated factors among home delivered mothers in Guto Gida District, East Wollega zone. - Mulugeta Abebe; Gemechu Kejela; Melese Chego; Markos Desalegn (Public Library of Science (PLoS), 2023)
Background Essential Newborn Care is a set of strategic and cost-effective interventions planned to improve the health of newborns through the care they receive from birth up to 28 days. In the current study area, little is known about the prevalence of essential newborn care practices and its associated factors. This study was aimed to assess the prevalence of essential newborn care practice and its associated factors among home-delivered mothers in Guto Gida district, western Ethiopia. Methods A community-based cross-sectional study was conducted in Guto Gida district from September 5 to 15, 2020. Data were collected by interviewing 601 systematically selected home-delivered women. Descriptive statistics were employed to describe frequency and percent. Binary logistic regression analysis was employed to identify candidate variables for the final model. Variables with p-value less than 0.25 at bivariate logistic regression were considered as the candidate variable and entered into multivariable logistic regression model. Finally, multivariable logistic regression was employed to identify associated factors at p-value less than 0.05, and the strength of association was described by adjusted odds ratios with 95% CI. Results The study shows that the level of essential newborn care practices was 168 (28%) (23.9-31.4). In this study, women in the first wealth quantile (AOR [95% CI] = 0.64 [0.34-0.97]), women who had one live birth (AOR [95% CI] = 0.51 [0.22-0.87]), women who lost their neonate before the study period (AOR [95% CI] = 0.11 [0.05-0.22]) were less likely to practice essential newborn care. Women who were advised on essential newborn care practice during a home visit by health extension workers (AOR [95% CI] = 3.45[1.56-7.26]), women who attended antenatal care during their current pregnancy (AOR [95% CI] = 1.79 (1.21-3.36]), and women who were attended at their birth by health extension workers (AOR [95% CI] = 3.29 [2.13-5.94]) were more likely to practice essential newborn care. Conclusions In this study, the prevalence of essential newborn care practice was low (28%), as compared with the World Health Organization recommendation that it should be 100%. The wealth quantile, number of live births, home visits by health extension workers, antenatal care, birth attendant, and neonatal death were independent predictors of essential newborn care practices.